2010
DOI: 10.1071/sr09150
|View full text |Cite
|
Sign up to set email alerts
|

Soil pH buffering capacity: a descriptive function and its application to some acidic tropical soils

Abstract: Calculation of soil acidification rates requires knowledge of pH buffering capacity (pHBC), which is measured using titration methods. The pHBC is often quoted as a single value for a particular soil, implying a linear relationship between pH and the amount of acid or alkali added. However, over its whole range, the relationship is sigmoid rather than linear, and in many soils pH is low or high enough to be outside of the linear range. In this work we fitted a simple sigmoid function to pH buffer curves of 8 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
76
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(106 citation statements)
references
References 19 publications
9
76
3
1
Order By: Relevance
“…2). These results were inconsistent with previous studies, which have shown that SOC content played an important role in soil pHBC (Aitken, 1992;Magdoff and Bartlett, 1985;Nelson and Su, 2010;Geissen et al, 2013). The discrepancy is probably caused by different types of organic matter involved (Nelson and Su, 2010).…”
Section: Effects Of Soil Properties On Soil Phbccontrasting
confidence: 57%
See 4 more Smart Citations
“…2). These results were inconsistent with previous studies, which have shown that SOC content played an important role in soil pHBC (Aitken, 1992;Magdoff and Bartlett, 1985;Nelson and Su, 2010;Geissen et al, 2013). The discrepancy is probably caused by different types of organic matter involved (Nelson and Su, 2010).…”
Section: Effects Of Soil Properties On Soil Phbccontrasting
confidence: 57%
“…Whereas acid inputs are fairly well documented, the patterns of soil pHBC across landscapes are not (Yang et al, 2012;Wong et al, 2013). Soil pHBC regulates the effect of acid deposition on terrestrial ecosystems by influencing the extent of soil pH change (Magdoff and Bartlett, 1985;Lu et al, 2015;Nelson and Su, 2010). Hence, measurement or estimation of soil pHBC is clearly beneficial for predicting the rate of soil acidification in response to predicted rates of acid deposition (Vet et al, 2014;Wong et al, 2013;Lu et al, 2015).…”
Section: W T Luo Et Al: Ph Buffering In Neutral-alkaline Soilsmentioning
confidence: 99%
See 3 more Smart Citations